THE IMPACT OF KNOWLEDGE AND TRUST OF CUSTOMERS ON PURCHASE INTENTION OF TELECOMMUNICATION SECTOR IN MALAYSIA - Yajid, Mohd Shukri Ab; kKhatibi, Ali; Sakinah (International Journal of Psychosocial Rehabilitation, 2020)
The aim of existing study is to inspect the effects of knowledge and trust on the purchase intention of the customers of telecommunication companies of Malaysia. Data were gathered form the head of the customer relation and SPSS was used for analysis. The results uncovered that positive nexus among the knowledge and trust with the purchase intention of the customers of telecommunication companies of Malaysia.